The seminal plasma microbiome of men with testicular germ cell tumours described by small RNA sequencing. (20th October 2022) - Mørup, Nina; Main, Ailsa Maria; Jørgensen, Niels; Daugaard, Gedske; Juul, Anders; Almstrup, Kristian
Abstract: Background: It has been estimated that microorganisms are involved in the pathogenesis of approximately 20% of all cancers. Testicular germ cell tumours (TGCTs) are the most common type of malignancy in young men and arise from the precursor cell, germ cell neoplasia in situ (GCNIS). The microbiome of seminal plasma and testicular tissue has not been thoroughly investigated in regard to TGCTs. Objectives: To investigate the differences in the seminal plasma microbiome between men with TGCT or GCNIS‐only compared with controls. Materials and methods: The study population consisted of patients with GCNIS‐only ( n = 5), TGCT ( n = 18), and controls ( n = 25) with different levels of sperm counts in the ejaculate. RNA was isolated from the seminal plasma and sequenced. Reads not mapping to the human genome were aligned against a set of 2784 bacterial/archaeal and 4336 viral genomes using the Kraken pipeline. Results: We identified reads from 2172 species and most counts were from Alteromonas mediterranea, Falconid herpesvirus 1, and Stigmatella aurantiaca . Six species ( Acaryochloris marina, Halovirus HGTV‐1, Thermaerobacter marianensis, Thioalkalivibrio sp. K90mix, Burkholderia sp. YI23, and Desulfurivibrio alkaliphilus ) were found in significantly ( q ‐value < 0.05) higher levels in the seminal plasma of TGCT and GCNIS‐only patients compared with controls. In contrast, Streptomyces phage VWB was found at significantly higher levels among controls compared with TGCT and GCNIS‐only patients combined. Discussion: Often the microbiome is analysed by shotgun or 16S ribosomal sequencing whereas our present data build on small RNA sequencing. This allowed us to identify more viruses and phages compared with previous studies but also makes the results difficult to directly compare. Conclusion: Our study is the first to report identification of the microbiome species in seminal plasma of men with TGCT and GCNIS‐only, which potentially could be involved in the pathogenesis of TGCTs. Further studies are, however, needed to confirm our findings.